Cost to government and society of chronic kidney disease stage 1-5: a national cohort study - Wyld, M.; Lee, Crystal; Zhuo, X.; White, S.; Shaw, J.; Morton, R.; Colagiuri, S.; Chadban, S. (Blackwell Publishing, 2015)
Background: Costs associated with chronic kidney disease (CKD) are not well documented. Understanding such costs is important to inform economic evaluations of prevention strategies and treatment options. Aim: To estimate the costs associated with CKD in Australia. Methods: We used data from the 2004/2005 AusDiab study, a national longitudinal population-based study of non-institutionalised Australian adults aged ≥25 years. We included 6138 participants with CKD, diabetes and healthcare cost data. The annual age and sex-adjusted costs per person were estimated using a generalised linear model. Costs were inflated from 2005 to 2012 Australian dollars using best practice methods. Results: Among 6138 study participants, there was a significant difference in the per-person annual direct healthcare costs by CKD status, increasing from $1829 (95% confidence interval (CI): $1740–1943) for those without CKD to $14 545 (95% CI: $5680–44 842) for those with stage 4 or 5 CKD (P < 0.01). Similarly, there was a significant difference in the per-person annual direct non-healthcare costs by CKD status from $524 (95% CI: $413–641) for those without CKD to $2349 (95% CI: $386–5156) for those with stage 4 or 5 CKD (P < 0.01). Diabetes is a common cause of CKD and is associated with increased health costs. Costs per person were higher for those with diabetes than those without diabetes in all CKD groups; however, this was significant only for those without CKD and those with early stage (stage 1 or 2) CKD. Conclusion: Individuals with CKD incur 85% higher healthcare costs and 50% higher government subsidies than individuals without CKD, and costs increase by CKD stage. Primary and secondary prevention strategies may reduce costs and warrant further consideration.